1997
DOI: 10.1021/ma970834a
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of the Polyalanine Repeats in Minor Ampullate Gland Silk of the Spider Nephila clavipes

Abstract: Solid state 13 C NMR is used to identify the conformation of alanine residues in minor ampullate gland silk from Nephila clavipes and in a genetically engineered protein based on the consensus sequence of MaSp2, a protein present in low concentrations in major ampullate gland silk. The results of the NMR on minor ampullate gland silk are compared to previous NMR data on major ampullate gland silk, and the results on the genetically engineered protein are compared to previous NMR data on the gland fibroin from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 19 publications
(54 reference statements)
3
42
0
Order By: Relevance
“…Solution state conformational studies using Fourier transform infrared spectroscopy (FTIR) of minor ampullate silk collected from N. edulis demonstrate a dominant α-helical nature, with reduced β-sheet structure [41]. Solid-state NMR data suggest that the conformations of the alanine residues found in minor ampullate silk fibers are more heterogeneous in nature, with a large fraction present in a non-β sheet conformation [42]. The lower amount of β-sheet structure, yet high tensile strength of the fiber, suggests that minor ampullate silks may have different cross-linking mechanisms and matrix proteins, relative to major ampullate silks.…”
Section: Minor Ampullate Silksmentioning
confidence: 99%
“…Solution state conformational studies using Fourier transform infrared spectroscopy (FTIR) of minor ampullate silk collected from N. edulis demonstrate a dominant α-helical nature, with reduced β-sheet structure [41]. Solid-state NMR data suggest that the conformations of the alanine residues found in minor ampullate silk fibers are more heterogeneous in nature, with a large fraction present in a non-β sheet conformation [42]. The lower amount of β-sheet structure, yet high tensile strength of the fiber, suggests that minor ampullate silks may have different cross-linking mechanisms and matrix proteins, relative to major ampullate silks.…”
Section: Minor Ampullate Silksmentioning
confidence: 99%
“…36,37,38 Like MaS, MiS contains polyalanine motifs, but they are shorter for the latter silk (n = 3-5) than for the former one (n = 5-7). 39 MiS also contains poly(Ala-Gly) sequences that are short as compared with those found in the Bombyx mori cocoon silk. MaS has two glycine repetitive blocks (GXX for MaSpI and GPGXX for MaSpII) 10,40 while MiS contains only GXX modules.…”
Section: Introductionmentioning
confidence: 99%
“…The variations in the mechanical behavior in dragline silk fibers across different species suggest that these silks have been fine-tuned by each spider for their nuanced needs. Other spider silk fiber types have also been studied using tensile testing, including aciniform silks (Hayashi et al, 2004), tubuliform silks (Hu et al, 2006a), flagelliform silks (Lewis, 2006) and minor ampullate silks (Liivak et al, 1997 Gosline et al 1999;Hayashi et al, 2004;Livak et al, 1997;Lawrence et al, 2004;Hu et al 2006a. nd = no data Table 2.…”
Section: Mechanical Properties Of Spider Silkmentioning
confidence: 99%
“…Similar to major ampullate silks, minor ampullate silks have been shown to display a high Young's modulus (Liivak et al, 1997). In addition, mechanical studies have demonstrated that aciniform silks represent the toughest spider silk type (Hayashi et al, 2004), a likely evolutionary adaptation to help prevent the escape of immobilized prey (Table 2).…”
Section: Minor Aciniform and Flagelliform Silkmentioning
confidence: 99%